Effect of tool offset distance variation and mechanical property evaluation for effective cladding of copper to steel by friction stir cladding - Mahto M.K.; Kumar A.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Deposition of copper on top of a steel substrate combines the advantages of the corrosion resistance of copper with the high tensile strength of steel. Due to their diverse properties, it is challenging to deposit copper on steel. In this work, the deposition of a 3 mm-thick copper layer has been carried out on top of a 6 mm thick steel substrate, utilizing the friction stir welding (FSW) process. During the process, several repetitive passes are required with a suitable tool offset to cover the entire plate effectively. A smaller tool pin offset results in the requirement of more passes, while too large a pin offset leaves the area between two passes unbonded. To optimize the tool offset distance, a series of trial experiments with offset values of 6, 8, 10, and 12 mm were carried out. Metallography examination along with X-ray radiography was carried out on the prepared clad samples. The average grain size of the steel substrate below the clad layer showed refined grains with a size of 5 μm, indicating an improvement of more than 60 % over the base steel. SEM and EDS map analysis revealed proper bonding of the cladding material with the substrate. Uniaxial tensile tests on flat specimens were carried out for base copper, base steel, and copper clad steel samples. The copper clad steel has a YS of 261 MPa and tensile strength of 359 MPa in comparison to the base copper, which has a YS of 131 MPa and a UTS of 227 MPa. Fractography analysis revealed stretching marks between copper and steel due to the difference in elongation rates of both materials. A guided bend test for face bend, root bend, and side bend revealed no delamination or crack initiation along the convex surface. Microhardness analysis was carried out across the interface from copper to steel, where a maximum hardness value of 226 HV was recorded near the interface close to the steel region. © 2023 The Society of Manufacturing Engineers